PENINGKATAN HASIL BELAJAR MELALUI MODEL PROBLEM BASED LEARNING PADA MATERI KPK DAN FPB DI KELAS VA SDN 01 MUNGKA KABUPATEN LIMA PULUH KOTA - Putri Orni Lisa; Refiona Andika; Salmaini Safitri; Sahrun Nisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low learning outcomes of fifth-grade students in mathematics learning on the Least Common Multiple (LCM) and Greatest Common Factor (GCF) materials at SDN 01 Mungka, Limapuluh Kota Regency. This study aimed to describe the planning, implementation, and improvement of students’ learning outcomes through the application of the Problem Based Learning (PBL) model on LCM and GCF materials. This research was a Classroom Action Research using qualitative and quantitative approaches. The research was conducted in two cycles, consisting of two meetings in Cycle I and one meeting in Cycle II. The subjects were 21 fifth-grade students of class VA at SDN 01 Mungka. Data were collected through observation, tests, and documentation and analyzed using qualitative and quantitative techniques. The results showed an improvement in lesson planning, teacher activity, student activity, and learning outcomes. The lesson planning score increased from 91% in Cycle I Meeting 1 to 95% in Cycle I Meeting 2 and 100% in Cycle II. Teacher activity increased from 75% to 89% and 96%, while student activity increased from 75% to 89% and 96%. Students’ average learning outcomes increased from 58.45 in Cycle I Meeting 1 to 75.57 in Cycle I Meeting 2 and 83.79 in Cycle II. In Cycle II, all 21 students achieved learning mastery. Thus, the application of the Problem Based Learning model can improve students’ learning outcomes in LCM and GCF mathematics learning.